1997
DOI: 10.1021/jo971046m
|View full text |Cite
|
Sign up to set email alerts
|

A Versatile and Highly Selective Hypervalent Iodine (III)/2,2,6,6-Tetramethyl-1-piperidinyloxyl-Mediated Oxidation of Alcohols to Carbonyl Compounds

Abstract: Catalytic amounts of 2,2,6,6-tetramethyl-1-piperidinyloxyl (TEMPO) are used in combination with [bis(acetoxy)iodo]benzene (BAIB) as a stoichiometric oxidant in the conversion of primary and secondary alcohols to carbonyl compounds. This procedure works efficiently at room temperature in almost all common solvents and neat in some cases. This process exhibits a very high degree of selectivity for the oxidation of primary alcohols to aldehydes, without any noticeable overoxidation to carboxyl compounds, and a hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
533
0
16

Year Published

1999
1999
2012
2012

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 771 publications
(557 citation statements)
references
References 50 publications
(25 reference statements)
8
533
0
16
Order By: Relevance
“…In the course of our studies, we incidentally found a novel oxidative lactonization of 1,6 diols using a catalytic amount of TEMPO and PhI(OAc) 2 as the stoichiometric oxidant. 48,49 To the best of our knowledge, application of these conditions to oxidative lactonization of 1,6 diols to construct seven membered lactones has not been reported. 50 The generality of this oxidative lactonization of 1,6 diols has been evaluated in our laboratory using various substrates and some examples are shown in Table 1.…”
Section: Second Generation Total Synthesismentioning
confidence: 99%
“…In the course of our studies, we incidentally found a novel oxidative lactonization of 1,6 diols using a catalytic amount of TEMPO and PhI(OAc) 2 as the stoichiometric oxidant. 48,49 To the best of our knowledge, application of these conditions to oxidative lactonization of 1,6 diols to construct seven membered lactones has not been reported. 50 The generality of this oxidative lactonization of 1,6 diols has been evaluated in our laboratory using various substrates and some examples are shown in Table 1.…”
Section: Second Generation Total Synthesismentioning
confidence: 99%
“…Purification of the residue by silica gel column chromatography (AcOEt:hexane = 25:75) gave 10 (48. 8 (12). A solution of 10 (348 mg, 366 mmol) in 60% aqueous acetic acid solution (8.0 ml) was stirred at 50 C for 20 min.…”
Section: Methyl 23-di-o-benzoyl--d-galactopyranoside (5)mentioning
confidence: 99%
“…Efficient methods for the conversion of alcohols to aldehydes, ketones or carboxylic acids under mild conditions have been developed, using TEMPO (2,2,6, 6-tetramethyl-1-piperidinyloxy), (I), as a catalyst and I) stoichiometric amounts of inexpensive, safe and easy to handle oxidants such as bleach [2], [bis(acetoxy) iodo] benzene (BAIB) [3], trichloroisocyanuricacid (TCCA) [4], oxone [5] or iodine [6].…”
Section: Introductionmentioning
confidence: 99%